First Blood A Cultural Study of Menarche - Dammery, Sally (Cultural Studies, 2015)
What woman forgets discovering her first period? First Blood examines the ways in which women from various countries - India, Sri Lanka, England, the Philippines, Greece, Italy, Uganda, Indonesia, Fiji, Chile, Ukraine, Korea, Singapore and Hong Kong - recall this moment of menarche and what it meant to them, their families, and their societies. What is the mystique of women's first blood? Blood is blood - or is it? What is the history of menstruation, and does this history belong to women? Who created the meanings associated with menarche, and why? Are there marked cultural differences? Have meanings changed over time? First Blood answers these questions and investigates beliefs and traditions surrounding menarche, including the concepts of uncleanness, ceremony, secrecy, and lore still existing in many parts of the world. The influence of the sanitary hygiene industry is also explored, as is the role of the pharmaceutical industry in making menstruation optional.